(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2023)
The Open Balkans initiative has received huge media attention for three reasons: first, because it is an authentic regional initiative launched by the leaders of Albania, North Macedonia and Serbia without foreign "mentorship"; second, because it has enabled practical mechanisms and measures that directly provide the economic sector of the participating countries to facilitate their business operations; and thirdly, because, unlike other initiatives with a regional character, it does not include all six economies of the Western Balkans, precisely because of existing political disagreements. The goal of this work is to determine and predict the real capacities of the Open Balkans, as well as the possibility of complete integration of the entire region within the framework of this initiative, aside to existing political disagreements. The research question is do the economic interests prevailed over the political interests of local politicians, so the future of this initiative is certain? In a theoretical sense, this paper will provide a new contribution to the science of international relations, more specifically in studies of regionalism by providing a new analysis of the importance of regional integration and association in the processes of economic development and political visibility of small and micro states, on the example of the Western Balkans.